Flat cross-section glass fiber, glass fiber reinforced resin composition, and glass fiber reinforced resin molded product
By using flat cross-section glass fibers with special shape ratios and filling rates to meet a specific range, the problems of oblong cross-section glass fibers are solved, and efficient chopped wire production and stability and strength of glass fiber reinforced resin molded products are achieved.
Patent Information
- Application Number
- CN202380022236.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-26
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-01-26
AI Technical Summary
The oblong cross-section glass fiber is severely worn when cut into chopped wire, resulting in low productivity. Different glass compositions lead to deterioration of productivity, making it difficult to maintain the dimensional stability and mechanical properties of glass fiber reinforced resin molded products.
Flat-section glass fibers are used, with a special-shaped ratio R in the range of 3.0 to 5.0, a filling rate P in the range of 77.0 to 92.0%, SiO2 in the glass composition is 52.0 to 62.0%, Al2O3 in 10.0 to 20.0%, and CaO in 16.7 to 28.1%, which satisfies a specific proportional relationship and is used to prepare a glass fiber reinforced resin composition.
It improves chopped wire productivity, maintains the same dimensional stability and bending strength, reduces the number of tool replacements, and improves production efficiency.
Abstract
Description
Technical Field
[0001] The present invention relates to flat cross-section glass fibers, glass fiber reinforced resin compositions and glass fiber reinforced resin molded products. Background Art
[0002] Conventionally, there is known a glass fiber reinforced resin molded product containing glass fibers (hereinafter sometimes referred to as flat cross-section glass fibers) including a plurality of flat cross-section glass filaments having a flat cross-section (see, for example, Patent Document 1).
[0003] In particular, the glass fiber reinforced resin molded product containing the following glass fiber (hereinafter, sometimes referred to as oblong cross-section glass filament) suppresses the occurrence of warping compared to the glass fiber reinforced resin molded product containing glass fiber including multiple glass filaments with a circular cross-section (hereinafter, sometimes referred to as circular cross-section glass fiber), and thus has excellent dimensional stability, and excellent mechanical properties such as tensile strength and bending strength, so it can be used in thin and short accessories such as portable electronic device housings. Among them, the oblong cross-section glass contains multiple flat cross-section glass filaments (hereinafter, sometimes referred to as oblong cross-section glass filaments) with an oblong cross-section shape (a shape in which the short side portions of a rectangle are replaced with semicircles with the short side as the diameter).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2020 / 137004 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, compared with the circular cross-sectional glass fibers, when the oblong cross-sectional glass fibers are cut into a predetermined length and processed into chopped strands, the cutting blades of the oblong cross-sectional glass fibers are more easily worn, and the number of replacement times of the cutting blades increases, resulting in a disadvantageous problem of poor chopped strand productivity.
[0009] In addition, the oblong cross-section glass fiber has a disadvantage that the productivity of the chopped strands described above is deteriorated due to the difference in glass composition of the glass constituting the glass fiber.
[0010] The object of the present invention is to provide a flat cross-section glass fiber, which can maintain the same mechanical properties such as dimensional stability and bending strength when made into a glass fiber reinforced resin molded product compared with the above-mentioned oblong cross-section glass fiber, and eliminate the above-mentioned undesirable conditions, and can obtain excellent short-cut strand productivity compared with oblong cross-section glass filaments.
[0011] Means for solving problems
[0012] In order to achieve the above-mentioned object, the glass fiber of the present invention is characterized in that it comprises a plurality of flat cross-sectional glass filaments having a flat cross-sectional shape, the major diameter of the cross-section of the flat cross-sectional glass filament is in the range of 20.0 to 35.0 μm, the minor diameter is in the range of 5.0 to 10.0 μm, the ratio of the major diameter to the minor diameter (major diameter / minor diameter), i.e., the profile ratio R, is in the range of greater than 3.0 and less than 5.0, the ratio of the cross-sectional area of the flat cross-sectional glass filament to the area of a rectangle circumscribed to the cross-sectional area of the flat cross-sectional glass filament (cross-sectional area of the flat cross-sectional glass filament / area of a rectangle circumscribed to the cross-sectional area of the flat cross-sectional glass filament), i.e., the filling rate P, is in the range of 77.0 to 92.0%, the profile ratio R and the filling rate P satisfy the following formula (1), and the glass fiber contains SiO in the range of 52.0 to 62.0 mass % relative to the total amount of the flat cross-sectional glass fiber. 2 , 10.0-20.0 mass% Al 2 O 3 and CaO in the range of 16.7 to 28.1 mass %.
[0013] 55.9≤P / R 1 / 4 ≤63.0…(1)
[0014] In the flat cross-section glass fiber of the present invention, it is preferred that the profile ratio R and the filling rate P satisfy the following formula (2).
[0015] 57.4≤P / R 1 / 4 ≤60.3…(2)
[0016] Furthermore, the glass fiber reinforced resin composition of the present invention is characterized in that the flat cross-section glass fiber of the present invention is contained in the resin composition.
[0017] Furthermore, the glass fiber reinforced resin molded article of the present invention is characterized in that it is composed of the glass fiber reinforced resin composition of the present invention.
[0018] According to the profile ratio R and the filling rate P, the formula (1) is satisfied and the SiO content in the range is contained relative to the total amount of the flat cross-section glass fiber. 2 、Al 2 O 3 The flat cross-section glass fiber of the present invention containing CaO and the glass fiber reinforced resin molded product of the present invention can maintain the same mechanical properties such as dimensional stability and bending strength as the glass fiber reinforced resin molded product containing oblong cross-section glass fiber, and can obtain excellent short strand productivity compared with the oblong cross-section glass fiber.
[0019] In addition, in the flat cross-section glass fiber of the present invention, if the content of CaO relative to the total amount of the flat cross-section glass fiber exceeds 28.1 mass %, the glass fiber reinforced resin molded product of the present invention cannot obtain sufficient mechanical properties such as bending strength. If the content of CaO relative to the total amount of the flat cross-section glass fiber is less than 16.7 mass %, the productivity of the chopped strands is reduced.
[0020] Here, being able to maintain the same dimensional stability compared to a glass fiber reinforced resin molded product containing oblong cross-section glass fibers means that the warpage of the glass fiber reinforced resin molded product measured by the measuring method described later is less than 5.0 mm. In addition, being able to maintain the same mechanical properties compared to a glass fiber reinforced resin molded product containing oblong cross-section glass fibers means that the flexural strength measured by the measuring method described later is more than 390 MPa.
[0021] Furthermore, being able to obtain excellent chopped strand productivity means that the number of blade replacements measured by a measuring method described later is less than 30 times.
[0022] Furthermore, by making the above-mentioned profile ratio R and the above-mentioned filling rate P of the flat cross-section glass fiber of the present invention satisfy the above-mentioned formula (2), it is possible to obtain a more excellent chopped strand productivity than that of the oval cross-section glass filament.
[0023] Here, being able to obtain a more excellent chopped strand productivity means that the number of blade replacements measured by the method described later is less than 20 times.
[0024] Furthermore, the glass fiber reinforced resin molded article of the present invention can maintain the same mechanical properties such as dimensional stability and bending strength as those of a glass fiber reinforced resin molded article containing oblong cross-section glass fibers.
[0025] Here, maintaining the same mechanical properties such as dimensional stability and bending strength as those of a glass fiber-reinforced resin molded product containing glass fibers having an oblong cross-section has the same meaning as described above. DETAILED DESCRIPTION
[0026] Next, embodiments of the present invention will be described in further detail.
[0027] The flat cross-section glass fiber of this embodiment includes a plurality of flat cross-section glass filaments having a flat cross-section shape, wherein the cross-section of the flat cross-section glass filament has a major diameter in the range of 20.0 to 35.0 μm, a minor diameter in the range of 5.0 to 10.0 μm, an irregularity ratio R in the range of greater than 3.0 and less than 5.0, and has a flat cross-section shape.
[0028] Here, the cross section of the flat cross-section glass filament refers to the cross section perpendicular to the length direction of the flat cross-section glass filament, and the above-mentioned profile ratio R is the ratio of the major diameter to the minor diameter (major diameter / minor diameter). In the flat cross-section glass fiber of the present embodiment, the above-mentioned profile ratio R is preferably in the range of 3.1 to 4.6, more preferably in the range of 3.4 to 4.4, and further preferably in the range of 3.7 to 4.2.
[0029] If the profile ratio R of the flat cross-section glass fiber of the present embodiment exceeds 5.0, the productivity of the chopped strands decreases, and if the profile ratio R is 3.0 or less, the glass fiber reinforced resin molded article of the present invention cannot obtain sufficient mechanical properties such as dimensional stability and flexural strength.
[0030] In addition, the filling rate P of the flat cross-section glass fiber of the present embodiment is in the range of 77.0 to 92.0%, the above-mentioned profile ratio R and the above-mentioned filling rate P satisfy the following formula (1), preferably satisfy the following formula (2), and the flat cross-section glass fiber contains SiO in the range of 52.0 to 62.0 mass % relative to the total amount of the flat cross-section glass fiber. 2 , 10.0-20.0 mass% Al 2 O 3 and CaO in the range of 16.7 to 28.1 mass %.
[0031] 55.9≤P / R 1 / 4 ≤63.0…(1)
[0032] 57.4≤P / R 1 / 4 ≤60.3…(2).
[0033] Here, the filling rate P is the ratio of the cross-sectional area of the flat cross-sectional glass filament to the area of the rectangle circumscribed with the cross-sectional area of the flat cross-sectional glass filament (cross-sectional area of the flat cross-sectional glass filament / area of the rectangle circumscribed with the cross-sectional area of the flat cross-sectional glass filament). In the flat cross-sectional glass filament of the present embodiment, the filling rate P is preferably in the range of 79.5 to 89.8%, more preferably in the range of 80.1 to 84.9%, further preferably in the range of 80.1 to 84.4%, particularly preferably in the range of 81.8 to 84.4%, and most preferably in the range of 82.0 to 84.0%.
[0034] In addition, if the filling rate P of the flat cross-section glass fiber of the present embodiment exceeds 92.0%, the cross-sectional shape is too close to a rectangle, so the productivity of the chopped strands is reduced. If the filling rate P is less than 77.0%, the cross-sectional shape is too close to an ellipse, so the glass fiber reinforced resin molded product of the present invention cannot obtain sufficient mechanical properties such as bending strength.
[0035] The glass composition of the glass forming the flat cross-section glass fiber of the present embodiment contains SiO in a range of 52.0 to 62.0 mass % based on the total amount of the flat cross-section glass fiber. 2 , 10.0-20.0 mass% Al 2 O 3 The glass composition preferably contains 52.0 to 56.0 mass % of SiO based on the total amount of the glass fibers. 2 , 12.0-16.0 mass% Al 2 O 3 , 20.0-25.0 mass % CaO and 0.0-10.0 mass % B 2 O 3 The composition is more preferably a composition containing SiO in a range of 53.0 to 55.0 mass % relative to the total amount of the glass fiber. 2 , 13.0-15.0 mass% Al 2 O 3 , 21.0-24.0 mass% CaO, 5.0-10.0 mass% B 2 O 3 The composition of the flat cross-section glass fiber may include, for example, the following glass composition (hereinafter sometimes referred to as composition A): containing 54.6% by mass of SiO 2 , 14.1 mass% Al 2 O 3 , 22.4 mass% CaO, 6.1 mass% B 2 O 3 , 1.2 mass% MgO, 0.3 mass% TiO 2 , a total of 0.5 mass% Na 2 O.K 2 O and Li 2 O, 0.6 mass% F 2 , 0.2 mass% Fe 2 O 3 .
[0036] When measuring the contents of the aforementioned components in the flat cross-section glass fiber of this embodiment, an ICP emission spectrometer can be used to measure the content of Li as a light element, and a wavelength dispersive fluorescent X-ray analyzer can be used to measure the contents of other elements.
[0037] The following method can be used as a measurement method: Specifically, first, a glass batch (a glass batch obtained by mixing and blending glass raw materials) or a flat cross-section glass fiber of the present embodiment (in the case where an organic substance is attached to the surface of the flat cross-section glass fiber or the flat cross-section glass fiber is mainly contained in an organic substance (resin) as a reinforcing material, for example, the organic substance is removed by heating in a muffle furnace at 300 to 600°C for about 2 to 24 hours, etc.) in a platinum crucible, and kept in an electric furnace at a temperature of 1550°C for 6 hours, while being stirred and melted, thereby obtaining a homogeneous molten glass. Then, the obtained molten glass is poured onto a carbon plate to form glass scraps, which are then crushed to powder to obtain glass powder. After the above-mentioned glass powder is heated and decomposed with an acid, Li as a light element is quantitatively analyzed using an ICP emission spectrophotometer. After the above-mentioned glass powder is formed into a disc shape using a press, other elements are quantitatively analyzed by the fundamental parameter method and using a wavelength dispersion type fluorescence X-ray analyzer. These quantitative analysis results are converted into oxides, the content and total amount of each component are calculated, and the content (mass %) of each component described above can be obtained based on these numerical values.
[0038] For example, the flat cross-section glass fiber of the present embodiment can be manufactured by the following method. First, a glass raw material (batch glass material) prepared in a manner to have a specified glass composition (for example, the above-mentioned composition A) is supplied to a melting furnace, and the glass raw material is melted at a temperature in the range of, for example, 1450 to 1550° C. Next, when the molten glass batch material (molten glass) is pulled out from 10 to 30,000 nozzle heads of a sleeve controlled to have a specified temperature and quenched, the nozzle heads are set to a non-circular shape, for example, a nozzle head having a shape corresponding to the cross-sectional shape of the flat cross-section glass filament and having a protrusion and a cutout portion that can quench the molten glass, and by controlling the temperature conditions, flat cross-section glass filaments can be obtained.
[0039] Next, a coating device is used to apply a bundling agent or adhesive, and a bundling shoe is used to bundle 10 to 30,000 flat cross-section glass filaments, and a winder is used to wind them onto a tube at high speed, thereby producing the flat cross-section glass fiber of this embodiment. In addition, in the flat cross-section glass fiber of this embodiment, more than 50% of the glass filaments constituting the flat cross-section glass fiber are the above-mentioned flat cross-section glass filaments, preferably more than 80% of the glass filaments are the above-mentioned flat cross-section glass filaments, more preferably more than 90% of the glass filaments are the above-mentioned flat cross-section glass filaments, and further preferably 100% of the glass filaments are the above-mentioned flat cross-section glass filaments.
[0040] The minor diameter and major diameter of the glass filaments contained in the flat cross-section glass fiber of the present embodiment can be adjusted by adjusting the major diameter and minor diameter of the nozzle head, the winding speed, the temperature conditions, etc. For example, by speeding up the winding speed, the minor diameter and major diameter can be reduced, and by slowing down the winding speed, the minor diameter and major diameter can be increased.
[0041] Examples of the flat cross-section glass fiber include glass yarn, glass fiber chopped strands, glass roving, glass powder, and glass fiber mat. In addition, the glass fiber may be in the form of glass cloth composed of glass yarn or glass yarn roving, chopped strand mat composed of glass fiber chopped strands, or in the form of glass filaments dispersed in a glass fiber reinforced resin molded product.
[0042] For example, when the flat cross-section glass fiber of the present embodiment is chopped strands, the number of flat cross-section glass filaments constituting the flat cross-section glass fiber is, for example, 10 to 20,000, preferably 50 to 10,000, and more preferably 1,000 to 8,000. In addition, the length of the chopped strands of the flat cross-section glass fiber of the present embodiment is, for example, 1.0 to 100.0 mm, preferably 1.2 to 51.0 mm, more preferably 1.5 to 30.0 mm, further preferably 2.0 to 15.0 mm, and particularly preferably 2.3 to 7.8 mm. Here, the chopped strands can be obtained by cutting the flat cross-section glass fiber obtained by the above method into the prescribed length using a known device such as a long fiber cutting device. Among them, the long fiber cutting device cuts the glass strands (flat cross-section glass fiber) fed between a cutter roll of a cutter (cutting blade) installed radially at equal intervals and a rubber roller that rotates in contact with the cutter roll and is equipped with rubber on the outer circumference into the prescribed length.
[0043] When the flat cross-section glass fiber of the present embodiment is a roving, the number of glass filaments constituting the flat cross-section glass fiber is, for example, 200 to 30000. The roving as the flat cross-section glass fiber of the present embodiment has a mass per unit area of 35 to 10000 tex (g / km).
[0044] In the case where the flat cross-section glass fiber of the present embodiment is glass powder (sometimes also referred to as cut fiber), the number of glass filaments constituting the flat cross-section glass fiber is, for example, 10 to 20,000. In addition, the length of the glass powder as the flat cross-section glass fiber of the present embodiment is, for example, 0.001 to 0.900 mm. Here, the glass powder can be made in the following manner: the flat cross-section glass fiber made by the above method is crushed into glass powder having the above specified length by a known method such as a ball mill or a Henschel disperser.
[0045] In the flat cross-section glass fiber of the present embodiment, the major axis and the minor axis of the cross section can be measured, for example, as follows.
[0046] First, in the case where the flat cross-section glass fiber of the present embodiment is not contained in the glass fiber reinforced resin molded product, the flat cross-section glass fiber is embedded in a resin such as an epoxy resin and the resin is cured, the cured resin is cut and its cross section is ground, and then the cross section of the cured resin is observed using an electron microscope. Then, for all the flat cross-section glass filaments or more than 200 filaments constituting the flat cross-section glass fiber exposed in the cross section of the cured resin, the longest side passing through the approximate center of the flat cross-section glass filament is taken as the major diameter, and the side orthogonal to the longest side at the approximate center of the flat cross-section glass filament is taken as the minor diameter, and the lengths of the major diameter and the minor diameter of each cross section are measured respectively.
[0047] In addition, when the glass fiber reinforced resin molded product contains the above-mentioned flat cross-section glass fiber, the glass fiber reinforced resin molded product is cut and its cross section is ground, and then the cross section of the resin is observed using an electron microscope. Then, for the above-mentioned flat cross-section glass filaments constituting the above-mentioned flat cross-section glass fiber exposed from the cross section of the above-mentioned resin, the longest side passing through the approximate center of the flat cross-section glass filament is taken as the major diameter, and the side orthogonal to the longest side at the approximate center of the flat cross-section glass filament is taken as the minor diameter, and the lengths of the major diameter and the minor diameter of each cross section are measured respectively.
[0048] Here, regardless of whether the glass fiber reinforced resin molded product contains the above-mentioned flat cross-section glass filaments or not, the major and minor diameters of the cross section of the above-mentioned flat cross-section glass filaments can be measured by processing the image obtained by an electron microscope using an automatic analysis device.
[0049] In the flat cross-section glass fiber of the present invention, the major diameter of the cross section of the above-mentioned flat cross-section glass filament is in the range of 20.0 to 35.0 μm, preferably in the range of 22.3 to 32.8 μm, more preferably in the range of 24.1 to 31.4 μm, further preferably in the range of 26.5 to 29.9 μm, and particularly preferably in the range of 27.0 to 28.8 μm.
[0050] In the flat cross-section glass fiber of the present invention, the short diameter of the cross section of the above-mentioned flat cross-section glass filament is in the range of 5.0 to 10.0 μm, preferably in the range of 5.5 to 9.0 μm, more preferably in the range of 6.1 to 8.4 μm, further preferably in the range of 6.5 to 7.9 μm, and particularly preferably in the range of 6.8 to 7.4 μm.
[0051] The major axis and minor axis of the above cross-section measured by the above method can be used to calculate the above profile ratio R in the form of the ratio of the major axis to the minor axis (major axis / minor axis).
[0052] In addition, the major axis and minor axis of the above cross-section measured by the above method can be used to calculate the area of the rectangle circumscribing the cross-section of the above flat cross-section glass filament in the form of the product of the minor axis and the major axis (minor axis × major axis). When measuring the major axis and minor axis of the above cross-section, well-known image analysis software such as “A Image-kun” (registered trademark, manufactured by Asahi Kasei Engineering Corporation) can be used to measure the cross-sectional area of the above flat cross-section glass filament.
[0053] Moreover, based on the area of the rectangle circumscribing the cross-section of the above flat cross-section glass filament and the cross-sectional area of the above flat cross-section glass filament, the above filling rate P can be calculated in the form of the ratio of the cross-sectional area of the flat cross-section glass filament to the area of the rectangle circumscribing the cross-section of the flat cross-section glass filament (cross-sectional area of flat cross-section glass filament / area of rectangle circumscribing the cross-section of flat cross-section glass filament).
[0054] The cross-sectional shape of the flat cross-section glass fiber of the present embodiment is preferably symmetric with respect to the longest side passing through the approximate center of the above flat cross-section glass filament.
[0055] In the flat cross-section glass fiber of the present embodiment, although the greater the filling rate P, the more obvious the improvement effect on the flexural strength and warpage of the glass fiber reinforced resin molded product of the present embodiment, there is a tendency for the spinnability and the short cut roving manufacturability to deteriorate. On the other hand, the greater the profile ratio R, the greater the improvement effect on the strength and warpage in the glass fiber reinforced resin molded product of the present embodiment, but the productivity of the short cut roving deteriorates. It is considered that formula (1) represents the balance of the above tendencies.
[0056] According to the flat cross-section glass fiber of the present embodiment, by making the profile ratio R and the filling rate P satisfy the formula (1), the glass fiber reinforced resin molded product of the present embodiment containing this flat cross-section glass fiber can maintain the same dimensional stability and mechanical properties such as flexural strength as the glass fiber reinforced resin molded product containing glass fibers with an oval cross-section, and can obtain excellent productivity of short cut rovings compared with glass fibers with an oval cross-section.
[0057] In addition, according to the flat cross-section glass fiber of the present embodiment, when the profile ratio R and the filling rate P satisfy the formula (1), the filling rate P is in the range of 80.1 to 84.9%. Therefore, the glass fiber reinforced resin molded product of the present embodiment can maintain the same dimensional stability as the glass fiber reinforced resin molded product containing the oblong cross-section glass fiber, and can obtain a better chopped strand productivity than the oblong cross-section glass filament.
[0058] In addition, according to the flat cross-section glass fiber of the present embodiment, when the above-mentioned profile ratio R and the above-mentioned filling rate P satisfy the above-mentioned formula (1), the above-mentioned filling rate P is in the range of 81.8 to 84.4%. Therefore, the glass fiber reinforced resin molded product of the present embodiment can obtain excellent mechanical properties while maintaining the same dimensional stability compared with the glass fiber reinforced resin molded product containing the oblong cross-section glass fiber, and can obtain better short-cut strand productivity compared with the oblong cross-section glass fiber.
[0059] Here, being able to maintain the same dimensional stability as a glass fiber reinforced resin molded product containing oblong cross-section glass fibers means that the warpage of the glass fiber reinforced resin molded product measured by the measuring method described later is 5.0 mm or less. In addition, being able to maintain the same mechanical properties as a glass fiber reinforced resin molded product containing oblong cross-section glass fibers means that the bending strength measured by the measuring method described later is 390 MPa or more, and being able to obtain excellent mechanical properties compared to a glass fiber reinforced resin molded product containing oblong cross-section glass fibers means that the bending strength measured by the measuring method described later is 400 MPa or more.
[0060] Furthermore, being able to obtain excellent chopped strand productivity means that the number of times the blade is replaced as measured by the measuring method described below is less than 30 times, and being able to obtain even better chopped strand productivity means that the number of times the blade is replaced as measured by the measuring method described below is less than 20 times.
[0061] [Measurement method for warpage of glass fiber reinforced resin molded products]
[0062] First, the surface of the flat cross-section glass fiber was coated with a composition containing a silane coupling agent, and the fiber was cut into 3 mm in length to prepare chopped strands. Next, a twin-screw mixer (manufactured by Shibaura Machine Co., Ltd., trade name: TEM-26SS) was used, the screw speed was set to 100 rpm, and the chopped strands and polyamide 6 resin (manufactured by Ube Industries, Ltd., trade name: UBE1015B) were mixed at a temperature of 270° C. to prepare resin pellets having a glass fiber content of 50% by mass.
[0063] Next, the resin pellets were used to perform injection molding using an injection molding machine (manufactured by Nissei Resin Industry Co., Ltd., trade name: NEX80) at a mold temperature of 80°C and an injection temperature of 270°C to obtain a flat plate having a size of 80 mm in length × 60 mm in width × 1 mm in thickness, i.e., a warpage test piece. When one corner of the warpage test piece was brought into contact with a flat surface, a vernier caliper was used to measure the distance between the corner located at a position diagonally opposite to the corner in contact with the flat surface and the flat surface. The distances were measured when the four corners of the warpage test piece were in contact with the flat surface, and the average of the measured values was taken as the warpage value.
[0064] [Measurement method for flexural strength of glass fiber reinforced resin molded products]
[0065] First, the resin pellets were injection molded using an injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., trade name: NEX80) at a mold temperature of 80° C. and an injection temperature of 270° C. to obtain a type A dumbbell test piece (thickness 4 mm) in accordance with JIS K7165:2008. A static bending test was performed using a precision universal testing machine (manufactured by Shimadzu Corporation, trade name: Autograph AG-5000B) at a test temperature of 23° C. in accordance with JIS (Japanese Industrial Standards) K 7171:2016 to measure the bending strength of the type A dumbbell test piece.
[0066] [Method for measuring chopped strand productivity]
[0067] The glass strands obtained by coating the surface of the flat cross-section glass fiber with a composition containing a silane coupling agent were cut into 3 mm lengths using a long fiber cutting device, and the number of times the cutter was replaced when manufacturing chopped strands for 240 hours was measured, wherein the long fiber cutting device was fed to cut the glass strands between a cutter roller having cutters (cutting blades) radially installed at equal intervals and a rubber roller rotating in contact with the cutter roller and equipped with rubber on the outer circumference.
[0068] In addition, by making the above-mentioned profile ratio R and the above-mentioned filling rate P of the flat cross-section glass fiber of the present embodiment satisfy the above-mentioned formula (2), the glass fiber reinforced molded product of the present invention can maintain the same dimensional stability as the glass fiber reinforced resin molded product containing oblong cross-section glass fiber, and can obtain a better chopped strand productivity compared with the oblong cross-section glass fiber.
[0069] Here, the meanings of being able to maintain the same dimensional stability as that of a glass fiber-reinforced resin molded product containing oblong cross-sectional glass fibers and being able to obtain a chopped strand productivity superior to that of oblong cross-sectional glass fibers are the same as described above.
[0070] Next, the glass fiber reinforced resin composition of the present embodiment contains the flat cross-section glass fiber of the present embodiment in a resin composition.
[0071] Next, the glass fiber reinforced resin molded product of this embodiment is composed of the glass fiber reinforced resin composition of this embodiment. The glass fiber reinforced resin molded product of this embodiment can maintain the same dimensional stability and mechanical properties as glass fiber reinforced resin molded products containing oblong cross-section glass fibers.
[0072] Here, the meaning of being able to maintain the same dimensional stability and mechanical properties as those of a glass fiber-reinforced resin molded product containing oblong cross-section glass fibers is the same as described above.
[0073] Examples of the resin composition constituting the glass fiber reinforced resin composition of the present embodiment include a resin composition containing a thermoplastic resin or a thermosetting resin.
[0074] Examples of the thermoplastic resin include polyethylene, polypropylene, polystyrene, styrene / maleic anhydride resin, styrene / maleimide resin, polyacrylonitrile, acrylonitrile / styrene (AS) resin, acrylonitrile / butadiene / styrene (ABS) resin, chlorinated polyethylene / acrylonitrile / styrene (ACS) resin, acrylonitrile / ethylene / styrene (AES) resin, acrylonitrile / styrene / methyl acrylate (ASA) resin, styrene / acrylonitrile (SAN) resin, methacrylic resin, polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), polyamide, polyacetal, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polycarbonate, polyarylene sulfide, polyether sulfone (PES), polyphenylene sulfone (PPSU), polyphenylene ether (PPE), modified polyphenylene ether (m-PPE), polyaryl ketone, liquid crystal polymer (LCP), fluororesin, polyetherimide (PES ... I), polyarylate (PAR), polysulfone (PSF), polyamideimide (PAI), polyaminobismaleimide (PABM), thermoplastic polyimide (TPI), polyethylene naphthalate (PEN), ethylene / vinyl acetate (EVA) resin, ionomer (IO) resin, polybutadiene, styrene / butadiene resin, polybutene, polymethylpentene, olefin / vinyl alcohol resin, cyclic olefin resin, cellulose resin, polylactic acid, etc.
[0075] Examples of the polyethylene include high-density polyethylene (HDPE), medium-density polyethylene, low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and ultra-high molecular weight polyethylene.
[0076] Examples of the polypropylene include isotactic polypropylene, syndiotactic polypropylene, atactic polypropylene, and mixtures thereof.
[0077] Examples of the polystyrene include general-purpose polystyrene (GPPS) which is atactic polystyrene having an atactic structure, high impact polystyrene (HIPS) obtained by adding a rubber component to GPPS, and atactic polystyrene having an atactic structure.
[0078] Examples of the methacrylic resin include polymers obtained by homopolymerizing one methacrylic resin selected from acrylic acid, methacrylic acid, styrene, methyl acrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, and fatty acid vinyl esters, and polymers obtained by copolymerizing two or more of the methacrylic resins.
[0079] Examples of the polyvinyl chloride include homopolymers of vinyl chloride polymerized by conventionally known methods such as emulsion polymerization, suspension polymerization, microsuspension polymerization, and bulk polymerization, copolymers of monomers copolymerizable with vinyl chloride monomers, and graft copolymers in which vinyl chloride monomers are graft-polymerized onto polymers.
[0080] Examples of the polyamide include polycaprolactam (polyamide 6), polyhexamethylene adipamide (polyamide 66), polybutylene adipamide (polyamide 46), polybutylene sebacamide (polyamide 410), polyadipamide (polyamide 56), polysebacamide (polyamide 510), polysebacamide (polyamide 610), polydodecamide (polyamide 612), polyadipamide (polyamide 106), polydecanediamide (polyamide 1010), polydodecanediamide (polyamide 1012), polyundecanamide (polyamide 11), polyundecanediamide (polyamide 116), polydodecanediamide (polyamide 12), polyxylene adipamide (polyamide XD6), polyxylene sebacamide (polyamide XD10), polyhexamethylene ad ...undecanediamide (polyamide 111), polyundecanediamide (polyamide 116), polydodecanediamide (polyamide 12), polyxylene adipamide (polyamide XD6), polyxylene sebacamide (polyamide XD10), polyhexamethylene adipamide (polyamide 106), polyxylene sebacamide (polyamide 1010), polydodecanediamide (polyamide 1012), polyhexamethylene adipamide ( m-phenylenediamine (polyamide MXD6), polyadipamide (polyamide PXD6), polybutylene terephthalamide (polyamide 4T), polypentamethylene terephthalamide (polyamide 5T), polyhexamethylene terephthalamide (polyamide 6T), polyisophthalamide (polyamide 6I), polynonane terephthalamide (polyamide 9T), polydecane terephthalamide (polyamide 10T), polyundecanediamine (polyamide 11T), polydodecane terephthalamide (polyamide 12T), polyisophthalamide (polyamide 4I), polybis(3-methyl-4-aminohexyl)methane terephthalamide (polyamide PACMT), polybis(3-methyl-4-aminohexyl)methane isophthalamide (polyamide PACM I), a polyamide selected from the group consisting of polybis(3-methyl-4-aminohexyl)methane dodecanamide (polyamide PACM12), polybis(3-methyl-4-aminohexyl)methane tetradecamide (polyamide PACM14), or a copolymer of two or more of the above components, and a mixture thereof.
[0081] Examples of the polyacetal include a homopolymer having an oxymethylene unit as a main repeating unit and a copolymer mainly composed of an oxymethylene unit and containing an oxyalkylene unit having 2 to 8 adjacent carbon atoms in the main chain.
[0082] Examples of the polyethylene terephthalate include polymers obtained by polycondensing terephthalic acid or a derivative thereof with ethylene glycol.
[0083] Examples of the polybutylene terephthalate include polymers obtained by polycondensing terephthalic acid or a derivative thereof with 1,4-butanediol.
[0084] Examples of the polytrimethylene terephthalate include polymers obtained by polycondensing terephthalic acid or a derivative thereof with 1,3-propylene glycol, and the like.
[0085] Examples of the polycarbonate include polymers obtained by an ester exchange method in which a dihydroxydiaryl compound is reacted with a carbonate such as diphenyl carbonate in a molten state, and polymers obtained by a phosgene method in which a dihydroxydiaryl compound is reacted with phosgene.
[0086] Examples of the polyarylene sulfide include linear polyphenylene sulfide, cross-linked polyphenylene sulfide that has a high molecular weight by a curing reaction after polymerization, polyphenylene sulfide sulfone, polyphenylene sulfide ether, and polyphenylene sulfide ketone.
[0087] Examples of the modified polyphenylene ether include polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and polystyrene, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / butadiene copolymer, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / maleic anhydride copolymer, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and polyamide, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / butadiene / acrylonitrile copolymer, and the like.
[0088] Examples of the polyaryletherketone include polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), and polyetheretherketoneketone (PEEKK).
[0089] As the above-mentioned liquid crystal polymer (LCP), there can be mentioned (co)polymers composed of one or more structural units selected from aromatic hydroxycarbonyl units, aromatic dihydroxy units, aromatic dicarbonyl units, aliphatic dihydroxy units, aliphatic dicarbonyl units, etc. which are thermotropic liquid crystal polyesters.
[0090] Examples of the fluororesins include polytetrafluoroethylene (PTFE), perfluoroalkoxy resin (PFA), fluorinated ethylene propylene resin (FEP), fluorinated ethylene tetrafluoroethylene resin (ETFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), and ethylene / chlorotrifluoroethylene resin (ECTFE).
[0091] Examples of the ionomer (IO) resin include copolymers of olefins or styrene and unsaturated carboxylic acids, wherein a part of the carboxyl groups are neutralized with metal ions.
[0092] Examples of the olefin / vinyl alcohol resin include ethylene / vinyl alcohol copolymers, propylene / vinyl alcohol copolymers, ethylene / vinyl acetate copolymer saponified products, and propylene / vinyl acetate copolymer saponified products.
[0093] Examples of the cyclic olefin resin include monocyclic compounds such as cyclohexene, polycyclic compounds such as tetracyclopentadiene, and polymers of cyclic olefin monomers.
[0094] Examples of the polylactic acid include poly-L-lactic acid which is an L-isomer homopolymer, poly-D-lactic acid which is a D-isomer homopolymer, and stereocomplex polylactic acid which is a mixture thereof.
[0095] Examples of the cellulose resin include methyl cellulose, ethyl cellulose, hydroxy cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, cellulose acetate, cellulose propionate, and cellulose butyrate.
[0096] In addition, examples of the above-mentioned thermosetting resins include: unsaturated polyester resins, vinyl ester resins, epoxy (EP) resins, melamine (MF) resins, phenolic resins (PF), polyurethane resins (PU), polyisocyanates, polyisocyanurates, polyimides (PI), urea-formaldehyde (UF) resins, silicone (SI) resins, furan (FR) resins, benzoguanamine (BR) resins, alkyd resins, xylene resins, bismaleimide triazine (BT) resins, diallyl phthalate resins (PDAP), and the like.
[0097] It should be noted that, in the flat cross-section glass fiber of the present embodiment, the flat cross-section glass filaments constituting the above-mentioned flat cross-section glass fiber may contact each other or may be separated from each other. When the above-mentioned flat cross-section glass filaments are separated from each other, a surface treatment agent or a resin composition constituting a glass fiber reinforced resin molded product may be present between the flat cross-section glass filaments.
[0098] Examples of the surface treatment agent include polyurethane resins, epoxy resins, vinyl acetate resins, acrylic resins, modified polypropylene, especially carboxylic acid-modified polypropylene, (poly)carboxylic acids, especially copolymers of maleic acid and unsaturated monomers, and silane coupling agents.
[0099] In addition, the flat cross-section glass fiber of the present embodiment may be coated with a composition including a lubricant, a surfactant, etc., in addition to being coated with these resins or silane coupling agents. Based on the mass of the flat cross-section glass fiber in a state not coated with the composition, the composition coats the flat cross-section glass fiber at a ratio of 0.1 to 2.0 mass %.
[0100] It should be noted that the coating of the flat cross-section glass fiber with an organic substance can be implemented in the following manner: for example, in the manufacturing process of the flat cross-section glass fiber, the above-mentioned sizing agent or adhesive containing the above-mentioned resin, the above-mentioned silane coupling agent or the above-mentioned composition solution is applied to the flat cross-section glass fiber using a known method such as a roller coater, and then the flat cross-section glass fiber coated with the above-mentioned resin, the above-mentioned silane coupling agent or the above-mentioned composition solution is dried.
[0101] Here, examples of the silane coupling agent include aminosilane, chlorosilane, epoxysilane, mercaptosilane, vinylsilane, acrylic silane and cationic silane. The silane coupling agent may be used alone or in combination of two or more thereof.
[0102] Examples of the aminosilane include γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-N′-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-anilinopropyltrimethoxysilane.
[0103] Examples of the chlorosilane include γ-chloropropyltrimethoxysilane and the like.
[0104] Examples of epoxysilane include γ-glycidoxypropyltrimethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0105] Examples of the mercaptosilane include γ-mercaptotrimethoxysilane and the like.
[0106] Examples of the vinyl silane include vinyltrimethoxysilane and N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane.
[0107] Examples of the acrylic silane include γ-methacryloxypropyltrimethoxysilane and the like.
[0108] Examples of the cationic silane include N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride and N-phenyl-3-aminopropyltrimethoxysilane hydrochloride.
[0109] Examples of lubricants include modified silicone oil, animal oil and its hydride, vegetable oil and its hydride, animal wax, vegetable wax, mineral wax, condensation product of higher saturated fatty acid and higher saturated alcohol, polyethyleneimine, polyalkyl polyamine alkylamide derivative, fatty acid amide, and quaternary ammonium salt. The above lubricants may be used alone or in combination of two or more.
[0110] Examples of animal oils include beef tallow and the like.
[0111] Examples of the vegetable oil include soybean oil, coconut oil, rapeseed oil, palm oil, and castor oil.
[0112] Examples of the animal wax include beeswax and lanolin.
[0113] Examples of the vegetable wax include candelilla wax and carnauba wax.
[0114] Examples of the mineral wax include paraffin wax and montan wax.
[0115] Examples of the condensate of a higher saturated fatty acid and a higher saturated alcohol include stearic acid esters such as lauryl stearate.
[0116] Examples of the fatty acid amide include dehydration condensates of polyethylene polyamines such as diethylenetriamine, triethylenetetramine, and tetraethylenepentamine, and fatty acids such as lauric acid, myristic acid, palmitic acid, and stearic acid.
[0117] Examples of the quaternary ammonium salt include alkyltrimethylammonium salts such as lauryltrimethylammonium chloride.
[0118] Examples of the surfactant include nonionic surfactants, cationic surfactants, anionic surfactants, and amphoteric surfactants. The surfactants may be used alone or in combination of two or more.
[0119] Examples of the nonionic surfactant include ethylene oxide oxypropylene alkyl ethers, polyoxyethylene alkyl ethers, polyoxyethylene-polyoxypropylene-block copolymers, alkyl polyoxyethylene-polyoxypropylene-block copolymer ethers, polyoxyethylene fatty acid esters, polyoxyethylene fatty acid monoesters, polyoxyethylene fatty acid diesters, polyoxyethylene sorbitan fatty acid esters, glycerol fatty acid ester ethylene oxide adducts, polyoxyethylene stearyl ethers, hydrogenated castor oil ethylene oxide adducts, alkylamine ethylene oxide adducts, fatty acid amide ethylene oxide adducts, glycerol fatty acid esters, polyglycerol fatty acid esters, pentaerythritol fatty acid esters, sorbitol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyhydric alcohol alkyl ethers, fatty acid alkanolamides, acetylene glycols, acetylene alcohols, ethylene oxide adducts of acetylene glycols, and ethylene oxide adducts of acetylene alcohols.
[0120] Examples of the cationic surfactant include alkyldimethylbenzylammonium chloride, alkyltrimethylammonium chloride, alkyldimethylethylammonium ethylsulfate, higher alkylamine acetates, higher alkylamine hydrochlorides, ethylene oxide adducts of higher alkylamines, condensates of higher fatty acids and polyalkylene polyamines, salts of esters of higher fatty acids and alkanolamines, salts of higher fatty acid amides, imidazoline-type cationic surfactants, and alkylpyridinium salts.
[0121] Examples of the anionic surfactant include higher alcohol sulfates, higher alkyl ether sulfates, α-olefin sulfates, alkylbenzene sulfonates, α-olefin sulfonates, reaction products of fatty acid halides and N-methyltaurine, dialkyl sulfosuccinates, higher alcohol phosphates, and phosphates of higher alcohol ethylene oxide adducts.
[0122] Examples of the amphoteric surfactant include amino acid-type amphoteric surfactants such as alkylaminopropionic acid alkali metal salts, and betaine-type and imidazoline-type amphoteric surfactants such as alkyldimethylbetaine.
[0123] As a molding method for obtaining the glass fiber reinforced resin molded product of the present embodiment, for example, there can be mentioned: injection molding, injection compression molding, two-color molding, hollow molding, foam molding (including foam molding using supercritical fluid), insert molding, in-mold coating molding, extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, blow molding, stamping, infusion, hand lay-up, spraying, resin transfer molding, sheet molding, bulk molding, pultrusion, filament winding, etc. Among these methods, injection molding is preferred because of its excellent manufacturing efficiency.
[0124] Next, examples of the present invention and comparative examples are shown.
[0125] Example
[0126] [Examples 1 to 4, Comparative Examples 1 to 7, Reference Example 1]
[0127] First, glass raw materials (glass batch materials) prepared in a manner to have any of the compositions A to C shown in Table 1 are supplied to a melting furnace, melted at a temperature range of 1450 to 1550°C, and the resulting molten glass is pulled out from a sleeve having 200 nozzle heads to produce a plurality of flat cross-section glass filaments, which are then bundled to produce flat cross-section glass fibers.
[0128] At this time, the nozzle head includes a hole portion and a wall portion, the hole portion has a flat cross-sectional shape with a long diameter of a predetermined length and a short diameter of a predetermined length, the wall portion includes a cutout portion for cooling the molten glass, and the length of the short diameter of the hole portion is adjusted to within a range of 0.2 to 2.0 mm, the ratio of the length of the long diameter of the hole portion to the length of the short diameter is adjusted to within a range of 2.0 to 8.0, and the amount of molten glass passing through each of the nozzle heads is adjusted to within a range of 0.1 to 3.0 g / min, thereby obtaining flat cross-sectional glass fibers of Examples 1 to 4 and Comparative Examples 1 to 7. It should be noted that the flat cross-sectional glass filaments of Comparative Example 5 are oblong cross-sectional glass filaments having an oblong cross-sectional shape, and the flat cross-sectional glass fibers of Comparative Example 5 are oblong cross-sectional glass fibers containing a plurality of oblong cross-sectional glass filaments.
[0129] Furthermore, the circular cross-sectional glass fiber of Reference Example 1 was obtained by providing the nozzle head with a hole portion having a true circular cross-sectional shape.
[0130] [Table 1]
[0131] Composition A Component B Composition C <![CDATA[SiO 2 (Mass %)]]> 54.6 59.3 54.5 <![CDATA[A1 2 O 3 (Mass %)]]> 14.1 19.0 14.6 CaO (mass%) 22.4 11.0 4.1 <![CDATA[B 2 O 3 (Mass %)]]> 6.1 0.5 19.4 MgO (mass%) 1.2 10.0 4.2 <![CDATA[TiO 2 (Mass %)]]> 0.3 0.0 1.9 <![CDATA[R 2 0(mass%)]]> 0.5 0.0 0.2 <![CDATA[F 2 (Mass %)]]> 0.6 0.0 1.0 <![CDATA[Fe 2 O 3 (Mass %)]]> 0.2 0.2 0.1 Total (mass %) 100.0 100.0 100.0
[0132] The short diameter, long diameter, profile ratio R, filling rate P and P / R of each flat cross-section glass filament of Examples 1 to 4 were 1 / 4 The values of are shown in Table 2. In addition, the minor diameter, major diameter, profile ratio R, filling rate P and P / R of each flat cross-section glass filament of Comparative Examples 1 to 7 and the circular cross-section glass filament of Reference Example 1 are shown in Table 2. 1 / 4 The values are shown in Table 3.
[0133] Next, the number of spinning breakages and the chopped strand productivity of each flat cross-section glass fiber of Examples 1 to 4, Comparative Examples 1 to 7, and the circular cross-section glass fiber of Reference Example 1 were measured by the following method. The number of spinning breakages and the chopped strand productivity of each flat cross-section fiber of Examples 1 to 4 are shown in Table 2. In addition, the number of spinning breakages and the chopped strand productivity of each flat cross-section glass fiber of Comparative Examples 1 to 7 and the circular cross-section glass fiber of Reference Example 1 are shown in Table 3.
[0134] 〔Number of spinning breaks〕
[0135] After 30 days of manufacturing each flat cross-section glass fiber of Examples 1 to 4, Comparative Examples 1 to 7 and the circular cross-section glass fiber of Reference Example 1, the number of times the flat cross-section glass filaments constituting each flat cross-section glass fiber of Examples 1 to 4, Comparative Examples 1 to 4, or the circular cross-section glass filaments constituting the circular cross-section glass fiber of Reference Example 1 were broken was measured. A shift is set to 8 hours, and the average number of breaks per shift is taken as the number of spinning breaks. The case where the number of spinning breaks per shift is less than 9 times is judged as "A", the case where the number of spinning breaks per shift is 9 times or more and less than 10 times is judged as "B", and the case where the number of spinning breaks per shift is 10 times or more is judged as "C".
[0136] 〔Productivity of chopped strands〕
[0137] The surfaces of the flat cross-section glass fibers of Examples 1 to 4, Comparative Examples 1 to 7, and the round cross-section glass fibers of Reference Example 1 were coated with a composition containing a silane coupling agent to obtain glass strands, and the glass strands were cut into 3 mm lengths using a long fiber cutting device. The number of times the cutter was replaced was measured 240 hours after the chopped strands were produced, and glass strands with less than 20 changes were judged as "A", glass strands with more than 20 changes but less than 30 changes were judged as "B", and glass strands with more than 30 changes were judged as "C". The long fiber cutting device is a device that cuts the glass strands between a cutter roller fed to a cutter (cutting blade) radially installed at equal intervals and a rubber roller rotating in contact with the cutter roller and equipped with rubber on the outer peripheral surface.
[0138] Next, each flat cross-section glass fiber of Examples 1 to 4 and Comparative Examples 1 to 7 and the round cross-section glass fiber of Reference Example 1 were coated with a composition containing a silane coupling agent, and each coated glass fiber was cut into a length of 3 mm to obtain chopped strands of Examples 1 to 4, Comparative Examples 1 to 7 and Reference Example 1. Next, each chopped strand and a polyamide 6 resin (Ube Industries, Ltd., trade name: UBE1015B) were kneaded at a temperature of 270° C. using a twin-screw kneader (manufactured by Shibaura Machine Co., Ltd., trade name: TEM-26SS) with the screw speed set to 100 rpm to prepare resin pellets of Examples 1 to 4, Comparative Examples 1 to 7 and Reference Example 1 having a glass fiber content of 50% by mass.
[0139] Next, each resin pellet was injection molded using an injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., trade name: NEX80) at a mold temperature of 80°C and an injection temperature of 270°C to obtain a flat plate having a size of 80 mm in length × 60 mm in width × 1 mm in thickness, i.e., a test piece for warpage measurement, and an A-type dumbbell test piece (thickness 4 mm) according to JIS K 7165:2008, which is a glass fiber reinforced resin molded product.
[0140] Next, the warpage of each warpage measurement test piece of Examples 1 to 4, Comparative Examples 1 to 7, and Reference Example 1 was measured by the following measurement method. In addition, the tensile strength and flexural strength of each A-type dumbbell test piece of Examples 1 to 4, Comparative Examples 1 to 7, and Reference Example 1 were measured by the following measurement method. The warpage, tensile strength, and flexural strength of the glass fiber reinforced resin molded products of Examples 1 to 4 are shown in Table 2. In addition, the warpage, tensile strength, and flexural strength of the glass fiber reinforced resin molded products of Comparative Examples 1 to 7 and Reference Example 1 are shown in Table 3.
[0141] 〔Warp〕
[0142] When one corner of the warpage test piece is brought into contact with a flat surface, the distance between the corner located at a diagonal position with the corner in contact with the flat surface and the flat surface is measured with a vernier caliper. The distances are measured when the four corners of the warpage test piece are in contact with the flat surface, and the average value of each measured value is 5.0 mm or less, which is judged as "OK", and the value is greater than 5.0 mm, which is judged as "NG".
[0143] 〔Tensile strength〕
[0144] The tensile strength of the A-type dumbbell test piece was measured by a static tensile test using a precision universal testing machine (manufactured by Shimadzu Corporation, trade name: Autograph AG-5000B) at a test temperature of 23°C in accordance with JIS K 7165: 2008. A test piece with a strength of 240 MPa or more was judged as "A", and a test piece with a strength of less than 240 MPa was judged as "B".
[0145] 〔Bending strength〕
[0146] The bending strength of the above-mentioned A-type dumbbell test piece was measured by a static bending test using a precision universal testing machine (manufactured by Shimadzu Corporation, trade name: Autograph AG-5000B) at a test temperature of 23°C in accordance with JIS K 7171: 2016. The test piece with a bending strength of 400 MPa or more was judged as "A", the test piece with a bending strength of 390 MPa or more and less than 400 MPa was judged as "B", and the test piece with a bending strength of less than 390 MPa was judged as "C".
[0147] [Table 2]
[0148] Example 1 Example 2 Example 3 Example 4 Glass composition A A A A Short diameter (μm) 7.0 7.5 67 7.2 Long diameter (μm) 28.0 26.0 29.0 28.5 Profile Ratio 4.0 3.5 4.3 4.0 Filling rate P(%) 83.0 80.5 81.0 86.8 P / R1 / 4 58.7 59.0 56.2 61.5 Tensile Strength A A A A Bending Strength A B B B Warping OK OK OK OK Spinning break times A A A B Chopped Strand Productivity A A B B
[0149] [Table 3]
[0150] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Reference Example 1 Glass composition A A A A A B C A Short diameter (μm) 7.5 7.2 6.2 7.0 7.0 7.0 7.0 11.0 Long diameter (μm) 28.3 28.3 29.7 28.0 28.0 28.0 28.0 11.0 Profile Ratio 3.8 3.9 4.8 4.0 4.0 4.0 4.0 1.0 Filling rate P(%) 91.0 78.0 82.3 91.1 94.6 83.0 83.0 78.5 <![CDATA[P / R 1 / 4 ]]> 65.3 55.4 55.6 64.4 66.9 58.7 58.7 78.5 Tensile Strength A B A A A A B B Bending Strength A B A A A A C C Warping OK NG OK OK OK OK OK NG Spinning break times C A C C C C A A Chopped Strand Productivity C A C C C C A A
[0151] It is obvious from Tables 2 and 3 that the flat cross-section glass fibers of Examples 1 to 4 are superior to the oblong cross-section glass fibers of Comparative Example 5 in that the glass fiber reinforced resin molded articles can maintain the same dimensional stability (warpage) and mechanical properties (bending strength) while having excellent chopped strand productivity.
[0152] On the other hand, according to P / R 1 / 4 The value of is outside the range of the above formula (1) and exceeds 63.0. It is obvious that the productivity of the chopped strands is poor. 1 / 4 The flat cross-section glass fibers of Comparative Examples 2 and 3, whose values are outside the range of the above formula (1) and are less than 55.9, have poor dimensional stability of glass fiber-reinforced resin molded products or poor chopped strand productivity.
[0153] In addition, it is obvious that although the above-mentioned profile ratio R and the above-mentioned filling rate P satisfy the above-mentioned formula (1), the flat-cross-section glass fibers of Comparative Examples 6 and 7, in which the content of CaO relative to the total amount of the flat-cross-section glass fibers is less than 16.7% by mass, also have poor chopped strand productivity or poor mechanical properties.
Claims
1. A flat cross-section glass fiber, characterized in that: The invention comprises a plurality of flat cross-section glass filaments having a flat cross-section shape, wherein the cross-section of the flat cross-section glass filaments has a major diameter in the range of 20.0 to 35.0 μm, a minor diameter in the range of 5.0 to 10.0 μm, and a ratio of the major diameter to the minor diameter (major diameter / minor diameter), i.e., a profile ratio R in the range of greater than 3.0 and less than 5.0, The ratio of the cross-sectional area of the flat cross-sectional glass filament to the area of the rectangle circumscribed to the cross-sectional area of the flat cross-sectional glass filament (cross-sectional area of the flat cross-sectional glass filament / area of the rectangle circumscribed to the cross-sectional area of the flat cross-sectional glass filament), i.e., the filling rate P, is in the range of 77.0 to 92.0%, and the profile ratio R and the filling rate P satisfy the following formula (1): The flat cross-section glass fiber contains SiO2 in a range of 52.0 to 62.0 mass %, Al2O3 in a range of 10.0 to 20.0 mass %, and CaO in a range of 16.7 to 28.1 mass % relative to the total amount of the flat cross-section glass fiber. 55.9≤P / R 1 / 4 ≤63.0…(1)。 2. The flat cross-section glass fiber according to claim 1, characterized in that: The profile ratio R and the filling rate P satisfy the following formula (2): 57.4≤P / R 1 / 4 ≤60.3…(2)。 3. A glass fiber reinforced resin composition, characterized in that: The flat cross-section glass fiber according to claim 1 or 2 is contained in a resin composition.
4. A glass fiber reinforced resin molded product, characterized in that: The glass fiber reinforced resin composition according to claim 3.
Citation Information
Patent Citations
Glass fiber-reinforced resin molded article
WO2020137004A1
Glass fiber-reinforced resin molded article
CN112469784A
Glass fiber-reinforced resin molded article
CN113474397A
Glass fibres for reinforcing oranic and / or inorganic materials
CN1243501A